The refractive indices of thin films of vacuum condensates cryo methane - Дробышев, А.С.; Соколов, Д.Ю.; Aбдуллaевa Ф.A.; Кaнтaевa М.Н.; Дуйсебaев Т.С. (Recent Contributions to Physics, 2016)
In this paper we investigate the dependence of the refractive index n of cryocondensates of CH4 from methane condensation temperature T. A comparative analysis of the values of refractive index n and density ρ cryocondensates methane CH4, ammonia NH3, carbon dioxide CO2 and water H2O. These values of the coefficients of refraction n of methane CH4 with decreasing condensation temperature T undergoes rupture in the vicinity of the phase transition temperature associated with the freezing of degrees of freedom of a quarter of molecules. The coefficient of refraction n of carbon dioxide CO2 with decreasing temperature T undergoes the greatest change at 77K 1.41 and 1.28 at 20K. For cryocondensation H2O water temperature changes did not affect the values of the refractive index, n. These results can be used in astrophysical research.